Distorsi Tujuan Pendidikan Islam di Era Modern: Bentuk, Faktor dan Langkah Preventif Pencegahannya - Syiehd Achmed Farhan; Winarnoko Winarnoko (YASIN, 2026)
Although Islamic education plays an important role in developing knowledge in the modern era, reality shows that Islamic education has not been fully able to respond appropriately to change, thereby giving rise to the phenomenon of distortion. This study aims to analyze the forms of distortion in the goals of Islamic education in the modern era, the factors that influence them, and preventive measures to address them. This study employed a qualitative approach with a library research design combined with a phenomenon study. The results showed that the distortion of Islamic education is reflected in the reduction of goals, the formalization of Islamic symbols, the dominance of cognitive aspects, and the weakening of the relationship between students and educators. These distortions are influenced by internal factors, such as the weak role of parents, a crisis in the concept and identity of Islamic education, curricula that are not yet holistic and innovative, as well as the quality and exemplary conduct of educators, as well as external factors, such as globalization, technological development, social dynamics, and the influence of Western culture. These findings affirm the need to reconstruct the goals of Islamic education based on tauhid, strengthen adab and morals, revitalize the role of educators as murabbi, and implement the principle of wasathiyah so that Islamic education is able to form human beings who are faithful, knowledgeable, and of noble character in a balanced manner. This study contributes to strengthening the study of Islamic education, particularly in understanding the distortion of educational goals and formulating preventive measures that are relevant to the challenges of the modern era.